Genotoxic consequences of viral infections - Olga Szewczyk-Roszczenko; Piotr Roszczenko; Yegor Vassetzky; Nikolajs Sjakste (npj Viruses)
Abstract Viral diseases continually threaten human health as evolving pathogens introduce new risks. These infections can lead to complications across organ systems, with impacts varying by virus type, infection severity, and individual immune response. This review examines the genotoxic stress caused by viral infections and its pathological consequences in humans.